The Transformation of Tolerance Attitudes Among Santri Gobal Gabul: A Multicultural Islamic Education Perspective - Habibi, Rohim; Wahyuni, Linna Endah Nur; Musfaah, Umi Robiatin (Fakultas Tarbiyah - Universitas Nahdlatul Ulama Sunan Giri, 2025)
This study explores the Santri Gobal Gabul community's contribution to shaping tolerance through a multicultural Islamic education framework. Employing a descriptive qualitative method with a phenomenological approach, data were gathered via in-depth interviews, participatory observation, and documentation involving pesantren caregivers, interfaith leaders, community figures, and local authorities. The findings indicate that the santri Gobal Gabul community is a transformative form of social spirituality expressed through inclusive leadership, moral exemplarity, sustained interfaith dialogue, and cross-cultural interaction. These practices have nurtured santri with tolerant, empathetic, and open-minded dispositions, enabling them to engage constructively across religious and cultural boundaries. Unlike conventional pesantren that emphasize formal structures, this organically developed community demonstrates a contextual model of Islamic education that is both dynamic and responsive to local realities. The study concludes that pesantren-based communities can serve as effective laboratories for tolerance education. The originality of this research lies in formulating a model of multicultural Islamic education rooted in local practice while reflecting universal Islamic values within the framework of national and human solidarity.